VERTICAL INTEGRATION AND THE EVOLUTION OF AUDIOVISUAL SERVICES: ECONOMIC POLICY IMPLICATIONS FOR BRAZIL - Mayo, John (Law, State and Telecommunications Review, 2020)
Purpose ”“ The purpose of this paper is describe the salience of economic theories and evidence regarding vertical integration in the multichannel audiovisual industry in Brazil. This is especially important at this time because Brazilian regulators and legislators are wrestling with the appropriate policy approach toward the industry in Brazil in the wake of the merger of AT&T and Time Warner. Methodology/approach/design ”“ The paper develops with several approaches. First, to develop context, the paper provides a high-level introduction to the evolution of the audiovisual industry. Second, the paper turns to a more specific assessment of the economic and legal lessons learned from the discussion and debate regarding the AT&T-Time Warner merger in the United States. This discussion draws on economic and legal theory and evidence, both from the published literature as well as from court proceedings to advance understanding of the issues. These foundational sections, in turn, provide a platform for policy insights. In particular, the paper builds upon earlier research on “results-based regulation” to provide guidance for Brazilian regulatory and legislative measures being considered in Brazil. Findings ”“ The paper concludes that a results-based approach should permit advances in the vertical integration of the audiovisual industry in Brazil. Such an approach necessarily would recognize that the modern evolution toward a more vertically integrated provisioning of audiovisual services is providing numerous consumer benefits while claims of consumer harm have been judged to be speculative. Application of Article 5 of SeAC to the AT&T-TW merger provides no additional consumer protections that are not already part of the merger and would, instead be distinctly anti-consumer.